Strategies for inclusive digital education: problem/project-based learning, cooperative learning, and service learning for students with special educational needs - D’Elia, Paola; Stalmach, Aleksandra; Di Sano, Sergio; Casale, Gino (Frontiers in Education, 2025)
IntroductionInclusive digital education is a growing field that aims to provide equitable learning opportunities for all students, including those with special educational needs (SEN). This study investigates the effectiveness of three pedagogical methods - problem/project-based learning (PBL), cooperative learning (CL), and service learning (SL) - in promoting inclusive digital education.MethodsWe adopted a quantitative approach, collecting data through a structured questionnaire administered to nine media education and pedagogy experts from Italy and Austria.ResultsResults showed that PBL, CL, and SL are generally effective but require differentiated implementation approaches to maximize inclusivity. Practical implementation in the inclusive context of PBL requires promoting student reflection and self-assessment adapted to students’ individual needs; in CL, group projects supported by digital collaboration tools (e.g., Google Docs) facilitate structured dialogue, peer collaboration, and shared responsibility, thereby increasing engagement; in SL, linking learning to real-world practice and designing experiences that reflect students’ abilities and interests emerge as crucial, especially for students with SEN.DiscussionThe implications of these findings suggest that educators should adopt flexible and adaptive strategies to successfully implement PBL, CL, and SL to ensure that they meet the diverse needs of students in digital environments. Limitations of the study and recommendations for future investigations are discussed to further develop this area of research.